Green Synthesis, Characterization and Photocatalytic Activity of Co3O4 Nanoparticles - Omar Mohammed; Ali Naghipour; Saeid Taghavi Fardood (Nanochemistry Research, 2025)
Co₃O₄ nanoparticles were synthesized using a green method and applied for photocatalytic degradation of tetracycline (TC) in aqueous solution. These nanoparticles were characterized using various techniques, including X-ray Diffraction (XRD), Ultraviolet-Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS), Transmission Electron Microscopy (TEM), Brunauer–Emmett–Teller (BET) analysis, Field Emission Scanning Electron Microscopy (FESEM), and Energy-Dispersive X-ray Spectroscopy (EDS) mapping techniques. The XRD pattern also revealed high crystallinity of the Co₃O₄ nanoparticles and confirmed their cubic crystal structure with a crystallite size of about 20 nm, as determined by the Scherrer equation. Further analysis of the sample by TEM indicated that the particle size was approximately 35 nm. The UV-Vis DRS analysis showed a band gap of 2.09 eV, supporting its potential as an effective photocatalyst. The BET analysis demonstrated that the surface area of the Co₃O₄ nanoparticles was 14.34 m²/g. The Co₃O₄ nanoparticles demonstrated strong photocatalytic activity, achieving 95% degradation of tetracycline within 3 hours under visible light at room temperature.